2017
DOI: 10.18632/oncotarget.17645
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of long noncoding RNAs in prostate cancer: a systematic review and meta-analysis

Abstract: The abnormally expressed LncRNAs played irreplaceable roles in the prognosis of prostate cancer (PCa). Therefore, we conducted this systematic review and meta-analysis to summarize the association between the expression of LncRNAs, prognosis and clinicopathology of PCa. 18 eligible studies were recruited into our analysis, including 18 on prognosis and 9 on clinicopathological features. Results indicated that aberrant expression of LncRNAs was significantly associated with biochemical recurrence-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
3
11
0
Order By: Relevance
“…There are also many types of lncRNAs that have been studied. Growing evidence suggests that lncRNAs are closely related with tumor . For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also many types of lncRNAs that have been studied. Growing evidence suggests that lncRNAs are closely related with tumor . For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence suggests that lncRNAs are closely related with tumor. [13][14][15][16][17][18] For example, lncRNA H19 promotes breast cancer progression, and plasma circulating lncRNA H19 can also serve as a screening and diagnostic marker for early breast cancer. 19 In endometrial carcinoma, it has been found that the expression profiles of lncRNAs are different between patients at early stage (stage I/II) and advanced stage (stage III/IV).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SChLAP1 knockdown determined a decrease of MMP-9, MMP-14, and VEGF expressions both in vitro and in vivo , confirming its involvement in cancer invasiveness and metastasis ( 49 ). All such findings show multiple interactions between SChLAP1 and factors involved in oncogenesis and cancer progression and explain the mechanism through which SChLAP1 promotes migration and invasion of PCa ( 50 ). Understanding this molecular pathway is essential for exploring new potential strategies for early diagnosis and therapy.…”
Section: Second Chromosome Locus Associated With Prostate-1mentioning
confidence: 90%
“…Each of these three lncRNAs has been shown to be upregulated in one or more types of cancer, and each one is commonly associated with poor patient prognosis. For example, LINC01123 is upregulated in intrahepatic cholangiocarcinomas (64) and is associated with poor prognosis in prostate cancer (65). Similarly, HOXD-AS2 is upregulated in glioma cells and is associated with poor prognosis (66).…”
Section: Discussionmentioning
confidence: 99%